Prediction of Mathematics Anxiety and Mathematics Performance by Teacher Characteristics in Secondary School Students - Kalami, Saeed; Mahigir, Foroogh; Babolmorad, Seyedeh Masoomeh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: This study aimed to examine the relationship between teacher characteristics and both mathematics anxiety and mathematics performance among secondary school students. Methods and Materials: Employing a descriptive-correlational research design, the study focused on a statistical population of high school students in Mysore, India. A sample of 400 students was selected using a multi-stage cluster sampling method. Participants completed the Mathematics Anxiety Scale (MAS), a mathematics achievement test (comprising problem-solving and calculation questions), and a teacher demographic questionnaire (including teacher age, education, and years of experience). Data were analyzed using multiple regression techniques. Findings: The findings indicated that teacher characteristics (age, education, and years of experience) were significantly negatively correlated with mathematics anxiety, while demonstrating a significant positive correlation with mathematics performance. Additionally, multivariate regression analysis revealed that the combination of these teacher characteristics serves as a strong predictor of both mathematics anxiety and mathematics performance. Conclusion: In light of these results and the importance of teachers’ educational qualifications in influencing mathematics anxiety and performance, it is recommended that teacher preparation and employment practices prioritize candidates with higher educational degrees. Furthermore, all teachers should receive comprehensive training in general, specialized, and pedagogical subjects through universities or other teacher preparation institutions.